The Relationship Between Knowledge and History of Dengue Hemorrhagic Fever and Community Participation as Foster Parents of the Wolbachia-Aedes Program in Tembalang Subdistrict, Semarang City - Kusariana, Nissa; Budiyanti, Rani Tiyas (Universitas Nahdlatul Ulama Surabaya, 2025)
The Wolbachia–Aedes technology was implemented in 2023 as part of the dengue control programme in Semarang City, with Tembalang Subdistrict designated as the pilot project area. In 2024, Tembalang recorded the highest incidence of dengue cases in the city. This study aimed to examine the relationship between knowledge and history of dengue hemorrhagic fever and community participation as foster parents (orang tua asuh / OTA) of the Wolbachia-Aedes program in Tembalang subdistrict, Semarang City.This study employed was a cross-sectional approach involving of all heads of families (Kepala Keluarga / KK) in Tembalang Subdistrict, Semarang City. A simple random sampling technique was used to select a sample of 110 families. The subject of this study consisted of individuals aged 17 years and older who resided in Tembalang Subdistrict. Data were colllected using a questionnaire and analyzed using chi-squared statistical test.The findings revealed that a relationship between the family history of dengue (p-value = 0.003) as well as the respondent's or family history of hospitalization due to dengue (p-value = 0.001) and community participation as foster parents. However, no relationship was found between the level of knowledge (p-value = 0.966) as well as the respondent’s history of dengue (p-value = 0.582) and community participation as foster parents. Keywords: knowledge, disease history, foster parents, dengue)